Le contrôle judiciaire des erreurs de droit en présence d'une clause privative - Garant, Patrice; Normand, Sylvio (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1982)
Administrative Tribunals have jurisdiction to deal with questions of law. In the exercise of such jurisdiction they may sometimes make mistakes in the construction of the statutes, regulations or other instruments. Even in the presence of a privative clause, an inferior tribunal should not be the supreme interpret of the law. It is one of the requirements of the « rule of law » that the Superior Court should have a supervisory « droit de regard ». Traditionally, only errors of law going to jurisdiction were out of the shield of the privative clause ; the Superior Courts used to restrain their intervention only after charactarizing the alleged error as « jurisdictional error of law ». Two difficulties came to arise from the approach about whether there exists an error of jurisdiction or one « merely » of law. Firstly, who can tell whether there is a genuine error of law. Secondly, what criteria transmute in the minds of Superior Court Judges an error into one of jurisdiction. The recent case law convinces us of the necessity of a different approach in order to achieve some clarity in this field of Administrative law. Mr. Justice Dickson of the Supreme Court of Canada hints at it in the Nispawin and the New Brunswick Liquor Corporation cases. This approach would put an end to the confusion that still prevail in other Supreme Court cases like Blanco or Labrecque. The distinction between errors of law going to jurisdiction and « merely » errors of law is unrational and so unpracticable that it should be abandoned and replaced by what we suggest in the following lines... Mr. Justice Robert Reid of the Ontario Divisional Court has also expressed the same concern in a remarquable judgment.